Application of a physically based hydrological model on a semi-arid watershed in Northern Ghana - Rudy, Arnold (My University, 1997)
Land degradation in semi-arid environments is increasing due to rapid population growth, poor landuse practices and variable climate conditions. Landuse planners require a better understanding of the impact that proposed changes in landuse practices have on a watershed’s hydrologic response when implementing policies and programs designed to decrease the detrimental effects of land degradation. A physically based hydrological model, r.hydro.CASC2D, was used to illustrate the impact changes in landuse practices have on the hydrologic response of a semi-arid watershed located in northern Ghana. The development of the required model input parameters using geographical information systems and remote sensing technologies is described. A sensitivity analysis on selected model inputs was conducted. The models output was sensitive to all model input parameter tested, such as grid cell size, Green and Ampt soil infiltration parameters and Manning’s n values. Two landuse scenarios were then developed to illustrate the impact of implementing landuse practices that increase vegetative ground cover. With increasing vegetative cover, peak discharges decreased with an associated delayed time to peak discharge. In addition, total runoff volume decreased as the level of vegetation increased, resulting in total volume of water infiltrating.
Keywords: Geographic information systems Ghana; Arid regions Ghana; Hydrologic models